Povazská Galéria Umenia Zilina 1976-1996. - Matustik, Radislav; Mazur, Milan; Rusnáková, Katarina (Zilina : Povazska Galeria Umenia, 1996)
Benka, Martin ; Bazovsky, Milos Alexander ; Fulla, Ludovit ; Kostka, Jozef ; Matejka, Peter ; Pribis, Rudolf ; Hloznik, Vincent ; Klimo, Alojz ; Uher, Rudolf ; Barcik, Andrej ; Fila, Rudolf ; Kompanek, Vladimir ; Pasteka, Milan ; Rudavsky, Andrej ; Bartusz, Juraj ; Jankovic, Jozef ; Koller, Julius ; Urbasek, Milos ; Zelibska, Jana ; Baron, Karol ; Brun, Robert ; Sigetova, Agnesa ; Kern, Michal ; Sikora, Rudolf ; Bockay, Milan ; Bockayova, Klara ; Fischer, Daniel ; Minarik, Igor ; Toth, Dezider ; Meluzin, Peter Igor ; Ronai, Peter ; Pichler, Karol ; Teren, Laco ; Ondák, Roman ; Grygar, Milan ; Ondreicka, Boris ; Tumarkin, Igael
Povazská Galéria Umenia Zilina / Museum of Art Zilina 1976-1996, Maj - August 1996
biografie, bibliografie
Slovaaks & Engels
kunstcatalogus